1996
DOI: 10.1111/j.1348-0421.1996.tb01150.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Japanese Encephalitis Virus in Okinawa

Abstract: In order to elucidate the molecular characteristics of Japanese encephalitis (JE) virus in Okinawa, 23 strains of JE virus isolated in a 25-year span were sequenced for the 240 nucleotides of the C-preM junction region and 111 nucleotides of the E gene region and compared with those of reference strains isolated in mainland Japan. The results of phylogenic analysis showed that although all the Okinawan isolates showed more than 96% homology in the nucleotide sequence in each region, they were chronologically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…[18][19][20][21][22][23] More than 150 strains of JEV have been isolated on Okinawa Island and all of the 23 sequenced isolates collected between 1968 and 1992 belonged to genotype 3. 24 Okinawan strains collected between 1986 and 1991 exhibited a different antigenic profile from the Nakayama and JaGAr#01 strains. 22 We conducted a genetic and sero-epidemiologic study of JEV to clarify the recent changes of its distribution on Okinawa Island.…”
Section: Introductionmentioning
confidence: 88%
“…[18][19][20][21][22][23] More than 150 strains of JEV have been isolated on Okinawa Island and all of the 23 sequenced isolates collected between 1968 and 1992 belonged to genotype 3. 24 Okinawan strains collected between 1986 and 1991 exhibited a different antigenic profile from the Nakayama and JaGAr#01 strains. 22 We conducted a genetic and sero-epidemiologic study of JEV to clarify the recent changes of its distribution on Okinawa Island.…”
Section: Introductionmentioning
confidence: 88%
“…Japan and Korea have recently reported the introduction of JEV G1 (Takegami et al, 2000;Nam et al, 1996;Ma et al, 2003). Ma et al (1996) reported that JEV strains in Japan isolated from 1968 to 1992 belong to G3. Most recently, Ma et al (2003) stated that Japanese JEV strains, mostly from swine serum, isolated between 1965 and 1991 clustered within G3, but all strains isolated from 1994 to 2001 clustered within G1.…”
mentioning
confidence: 99%
“…1 The geographic variation of JEV strains was demonstrated by the studies of RNA finger-prints 2,3 and nucleotide sequencing. [4][5][6][7][8][9][10] The genomic diversity of JEV has been determined by primer extension sequencing of the capsid/pre-membrane (C/prM) gene region. 4,5 These analyses indicated that JEV strains could be classified into four geographically distinct genotypes based on the nucleotide differences of more than 12%.…”
mentioning
confidence: 99%
“…The RNA of JEV-infected C6/36 cells was amplified by a reverse transcriptase−polymerase chain reaction with a pair of primers (JE317 and JE821R), 14 followed by sequencing as previously described. 8 Phylogenetic analyses were then performed on sequence information for a 240-nucleotide region of the C/prM gene. 4,5 A FIGURE 2.…”
mentioning
confidence: 99%